Serological responses to rotavirus NSP2 following administration of RV3-BB human neonatal rotavirus vaccine. Issue 8 (3rd August 2018) - Cowley, Daniel; Pavlic, Daniel; Bogdanovic-Sakran, Nada; Boniface, Karen; Kirkwood, Carl D.; Bines, Julie E.
ABSTRACT: Serum rotavirus IgA responses are an imperfect non-mechanistic correlate of protection, and the lack of an accurate serological marker is a challenge to the development of new rotavirus vaccines. Serological responses to rotavirus NSP2 occur following wild-type infection; however, it is unknown if serological responses to NSP2 occur following administration of rotavirus vaccines. The phase IIa immunogenicity trial of RV3-BB provided an opportunity to investigate the serological responses to NSP2 following vaccination. Healthy, full-term babies (n = 96) were previously recruited as part of a phase IIa safety and immunogenicity trial in Dunedin, New Zealand between January 2012 and April 2014. Participants received three doses of oral RV3-BB vaccine with the first dose given at 0–5 days after birth (neonatal schedule), or the first dose given at about 8 weeks after birth (infant schedule), or to receive placebo (placebo schedule). Serum IgA and IgG antibody responses to total RV3-BB and NSP2 protein (RV3-BB) were assessed using ELISA. Despite significant serum IgA response against total RV3-BB, we were unable to demonstrate a significant serological response to NSP2 in participants receiving RV3-BB when compared to placebo. Heterotypic antibodies against multiple NSP2 genotypes were detected following RV3-BB vaccination. Our data demonstrates that while serological responses to NSP2 were detectable in a subset of participants, it is a less useful marker when compared to total rotavirus serum IgA response.